ANALYSIS OF PUBLIC TRANSPORTATION MODE CHOICE OF GENERATION Z EMPLOYEES IN SUBURBAN AREAS - Widiyanto, Haya Haura; Sebayang, Karuniana Dianta Arfiando; Zahra, Siti Fatimah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
The high level of congestion in Jakarta City due to commuter activity from buffer areas underlies the urgency of shifting public preferences, especially Generation Z as a vital worker segment, from private transportation to public transportation. This quantitative research aims to analyze the influence of travel costs, travel time, and accessibility on the choice of public transportation modes by 114 Generation Z workers domiciled in buffer cities namely Bogor, Depok, Tangerang, Bekasi who work in Jakarta, using multiple linear regression analysis. The results of the study indicate (1) travel costs have no significant influence on the choice of public transportation, (2) travel time has a negative and significant influence on the choice of public transportation, and (3) accessibility is proven to have a positive and significant influence on the choice of public transportation. The results of the study indicate the need for the government and transportation service providers to prioritize increasing the efficiency of travel time and accessibility through the development of integrated infrastructure and first-mile/last-mile solutions, as well as maintaining affordability and ease of multi-modal transactions.